Interplay of Eph-Ephrin Signalling and Cadherin Function in Cell Segregation and Boundary Formation - Wilkinson, David G. (Frontiers in Cell and Developmental Biology, 2021)
The segregation of distinct cell populations to form sharp boundaries is crucial for stabilising tissue organisation, for example during hindbrain segmentation in craniofacial development. Two types of mechanisms have been found to underlie cell segregation: differential adhesion mediated by cadherins, and Eph receptor and ephrin signalling at the heterotypic interface which regulates cell adhesion, cortical tension and repulsion. An interplay occurs between these mechanisms since cadherins have been found to contribute to Eph-ephrin-mediated cell segregation. This may reflect that Eph receptor activation acts through multiple pathways to decrease cadherin-mediated adhesion which can drive cell segregation. However, Eph receptors mainly drive cell segregation through increased heterotypic tension or repulsion. Cadherins contribute to cell segregation by antagonising homotypic tension within each cell population. This suppression of homotypic tension increases the difference with heterotypic tension triggered by Eph receptor activation, and it is this differential tension that drives cell segregation and border sharpening.